PENERAPAN MODEL PEMBELAJARAN ROLE PLAYING UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI KELAS V SDN 017 JAYA KOPAH KECAMATAN KUANTAN TENGAH - Aulia Nur Andini; Andrizal Andrizal; Ikrima Mailani (Universitas Islam Kuantan Singingi, 2022)
This research is based on the lack of creativity in the use of methods in learning so that it becomes a factor that causes the lack of interest of students in Islamic Religious Education subjects. The application of the Role Playing Learning Model can increase students' interest in learning, this can be seen from the results of distributing student interest questionnaires in cycle I, cycle II, and cycle III. In the first cycle, the percentage of the learning interest questionnaire was 45%. For the second cycle, the distribution of student learning interest questionnaires was 80%. Meanwhile, for the third cycle, the distribution of student learning interest questionnaires was 90%. So based on the results of these studies, it can be concluded that the application of the Role Playing Learning Model can increase the interest in learning PAI for V grade students at SDN 017 Jaya Kopah.